EVALUASI RASIONALITAS PENGGUNAAN OBAT ANTIHIPERTENSI TERHADAP PASIEN HIPERTENSI DI RSUD KARAWANG - Himyatul Hidayah; Maya Arfania; Peggy Novita Sarie; Surya Amal (Jurnal Buana Farma, 2023)
Hypertension is a disease characterized by an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements, with an interval of five minutes in a state of sufficient rest/calm. This study aims to determine the relationship between hypertension and the patient's gender and age on the incidence of hypertension and the rationality of using antihypertensive drugs in hypertensive patients at the Karawang Hospital Outpatient Installation in 2019. This research is an observational study with a cross-sectional descriptive analysis design. Data collection was carried out retrospectively using secondary data from medical records taken from Karawang Hospital in 2019 at Karawang Hospital. Next, calculate the use of antihypertensive drugs and evaluate the rationale for using antihypertensive drugs in hypertensive patients based on the right patient, right indication, right drug, and the right dose. Data were obtained for 60 patients compared to Dipiro and JNC VIII guidelines. The results showed that the most widely used antihypertensive drugs were amlodipine 15% and a combination of 2 drugs (amlodipine and candesartan) 85%. Evaluation of the rationality of using hypertension drugs in hypertensive patients as follows: right drug 91.7%, right indication 100%, right patient 100%, right dose 91.7% and there is no relationship between gender and age of the patient to the incidence of hypertension in Karawang Hospital.